Exchange rate exposure revisited in Malaysia: a tale of two measures - Jaratin Lily; Imbarine Bujang; Abdul Aziz Karia; Mori Kogid (2018)
This paper investigates a tale of two measures, which are market portfolio returns and exchange rate movements. The two measures are important risk factors which affect firm share returns. This study also demonstrates that the orthogonalized exchange rate exposure model is better at capturing the effects of exchange rate movements towards large Malaysian firm share returns. In addition to this, it was found that there were not significant differences in terms of number of exposed firms to exchange rate movements, when the Trade Weighted Index (TWI) and multi bilateral exchange rates were used, both in nominal and real terms. The study results also have shown that large Malaysian firms, including financial firms, were exposed to exchange rate movements regardless their level of foreign involvement. Interestingly, most of the exposed large firms are negatively affected when there is depreciation on home currency especially to the US Dollar (USD) and Japanese Yen (JPY). Even though the exchange rate volatility has failed to solve the exchange rate exposure puzzle among large firms in Malaysia, but the high level of sensitivity for most of the firm share returns to exchange rate volatility should not be ignored. Policymakers and financial managers should closely monitor the foreign exchange markets to mitigate the negative impact of exchange rate movements. Future research should also look into the possibility that the relationship between exchange rate movements and share returns is asymmetric.